Occurrence of mycotoxin-producing fungi in coffee beans marketed in Goiás - Lima, Jacqueline Farias Rodrigues de; Falcão, Heloísa Gabriel; Machado, Simone Silva; Miguel, Keyla de Oliveira Ribeiro; Blanco , Angel José Vieira (Seven Editora, 2023)
Fungi constitute a heterogeneous group of microorganisms with diverse ecological activity. Many fungi are useful to mankind, while others are quite harmful. Besides being spoilage organisms, some genera of fungi are toxigenic and produce dangerous secondary metabolites called mycotoxins. Mycotoxins are low molecular weight, thermo-resistant compounds that can be found in various components of human food. Coffee is one of the foodstuffs with the highest incidence of toxigenic fungi, and the presence of these organisms can cause serious health problems in those who consume the beverage prepared. The absence of good practices along the production chain facilitates the development of these fungi, especially species of Aspergillus, Fusarium, and Penicillium. Some studies show that the mycotoxins produced by these fungi are not eliminated during the process of roasting the beans or after boiling the coffee, which shows the importance of detecting their presence, in a preventive way, before the roasting stage. The present work evaluated the occurrence of mycotoxin-producing fungi in coffee beans, commercialized in the raw form, dry, unshelled, and ready to be roasted, of five different brands commercialized in Goiás. Coffee beans were inoculated in a BDA medium and after the formation of colonies, microcultures were performed on slides for further identification. The results showed high levels of fungal contamination, with a predominance of Aspergillus niger, a species commonly found in soils, which produces one of the most potent mycotoxins known, ochratoxin A. DOI:https://doi.org/10.56238/devopinterscie-230